Extended producer responsibility in developing economies: Assessment of promoting factors through retail electronic firms for sustainable e-waste management. Issue 1 (January 2023) - Faibil, Daniel; Asante, Richard; Agyemang, Martin; Addaney, Michael; Baah, Charles
The adoption of the extended producers' responsibility (EPR) principle as a mitigation strategy for e-waste management has gained impetus over the past few years. However, e-waste management in developing economies through retail electronic firms' or producer responsibility organization is still inceptive. This study identified and analysed promoting factors of EPR principle adoption through retail electronic firms in the Ghanaian electronic industry. Through extant literature and stakeholders' perspectives, 15 factors were identified as strategic and operational promoting factors, which were evaluated by experts. Subsequently, the grey Decision-Making Trial and Evaluation Laboratory technique was used to analyse the data obtained. The outcome of the study suggests that operational factors have more influence than strategic factors to determine the adoption of the EPR principle. In addition, most of the important operational factors tend to be enabled by both push and pull measures by supply chain stakeholders. In the short term, adopting an advanced deposit recycling refund scheme tends to be the most effective elementary operational factor, which can push retailers to adopt the EPR principle. The significant pull elementary factors that need short-term attention include the opening up and creation of new market opportunities for e-companies as well as resilient and effective resources management. The study findings suggest that Ghana's present policy framework is limited for the adoption of the EPR principle by retail electronic firms. The study contributes to identifying promoting factors for adoption of the EPR principle from the perspectives of both the external and internal stakeholders in the electronic industry with emphasis on push and pull strategy.